Desempenho de crianças brasileiras nos subtestes de execução da escala de inteligência wechsler (4 – edição) - PAZ, Carlos Eduardo Dias Oliveira da (Universidade Federal do Pará, 2019)
This study will address the performance assessment on the WISC´s execution subtests in public and particular school children in the city of Belém in the state of Pará. The targer age group for this project will be from 06 years and 01 month until 16 years and 11 months. The chosen tool to perform this project will be the Wechsler Intelligence Scale for Children – Fourth Edition Brazilian (WISC IV). The assessment will still have as objectives the development of data which will be compared to the North-American samples for the padronization of the WISC IV. It´s worth to highlight that the application of the scale will be complete. The motor performance of the child can be studied through mensuration of the observable behavior, through psychometric tests or assessment by psychological testes that utilize standard scales. In Brazil the utilization of the WISC Scale is wide. The study of learning factors in a city like Belém will be of major importance for the knowledge of performance problems in education in the city, but mainly for helping in the elucidation of the relation between the neuropsychological motor development and culture.